Pengaruh Pemberian Tepung Bangun-Bangun (Coleus Amboinicus. L) pada Ransum Babi Terhadap Konversi Ransum Induk Menyusui dan Pertambahan Bobot Badan Anak - Sinaga, S.; Silalahi, M. (Jurnal Penelitian Pertanian Terapan, 2011)
This research has been done in the animal husbandry of Cigugur, Kuningan , Jawa Barat November 1st - December 16th, 2010 with intention of knowing the level of Coleus amboinicus. L giving and the effect of Coleus amboinicus. L flour giving towards the weight gain of piglet. Fifteen sows with weight around 125-150 kg each have been allocated into the Complete Random Design three treatment rations and have been repeated five times. The combination of treatment ration consists of R0 (Ration with 0% of Coleus amboinicus. L flour), R1 (ration with 3% of Coleus amboinicus. L flour), R3 (ration with 5% of Coleus amboinicus. L flour). Based on the result of the research, it can be concluded that the giving of Coleus amboinicus. L flour in the amount of 5% gives effect forwards the weight gain of piglet and the ration conversion. Keywords: Coleus ambonicus L flour, Conversion Ration Sow, Sow During Lactation, Weight Gain of Piglet